Phenolics and neolignans isolated from the fruits of Juglans mandshurica Maxim. and their effects on lipolysis in adipocytes. (May 2017) - Park, SeonJu; Kim, Nanyoung; Yoo, Guijae; Kim, Sang-Nam; Kwon, Hyun-Jung; Jung, Kiwon; Oh, Dong-Chan; Lee, Yun-Hee; Kim, Seung Hyun
Abstract: Juglans mandshurica Maxim. (Juglandaceae) is a traditional folk medicine used for treatment of dermatosis and to relieve aches in Korea and China. In this study, eight compounds, along with six known compounds, were isolated from the fruit of J. mandshurica . Among the six known compounds, the absolute configuration of two compounds were determined. The structures of compounds were determined on the basis of extensive spectroscopic methods, including 1D and 2D NMR and CD spectroscopic data. All isolated compounds were tested for their lipolytic activities in differentiated adipocytes using C3H10T1/2 mouse embryonic fibroblasts. Among them, 2-(4-formyl-2-methoxyphenoxy)-propan-1, 3-diol and 2-[4-(3-hydroxypropyl)-2-methoxyphenoxy]-1, 3-propanediol exhibited the most potent lipolytic activities. Graphical abstract: Eight compounds, along with six known compounds, were isolated from the fruit of J. mandshurica . 2-(4-Formyl-2-methoxyphenoxy)-propan-1, 3-diol and 2-[4-(3-hydroxypropyl)-2-methoxyphenoxy]-1, 3-propanediol exhibited the most potent lipolytic activities in differentiated adipocytes using C3H10T1/2 mouse embryonic fibroblasts. Highlights: Eight compounds were isolated from the fruit of Juglans mandshurica . All compounds were tested for their lipolytic activities in C3H10T1/2. 2-(4-Formyl-2-methoxyphenoxy)-propan-1, 3-diol showed the best activity compared to the positive control.